Mikrokontroler dalam Sistem Informasi Manajemen Proyek TI : Solusi Modern untuk Tantangan Proyek Digital - Widya Ari Rizki (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The rapid development of digital technology has introduced new challenges in IT project management. Microcontrollers, typically used in hardware systems, offer innovative solutions to address these challenges. This article aims to explore the role of microcontrollers in IT project management information systems, focusing on task automation, real-time data collection, and IoT device management. The research examines the application of microcontrollers in optimizing efficiency and accuracy in managing digital projects. Key findings indicate that microcontrollers can significantly enhance monitoring, control, and analysis of projects, providing better insights for project managers in making strategic decisions. In conclusion, microcontrollers offer effective modern solutions to current digital project challenges.